Analisis Strategi Komunikasi Publik Samsat Kota Padang Dalam Mensosialisasikan Program Pemutihan Pajak Tahun 2025 - Julia Delka Cahyani; Dion Eriend (CV. ITTC INDONESIA, 2026)
This study analyzes the public communication strategy carried out by the Padang City Samsat in socializing the 2025 tax amnesty program. The tax amnesty program is a regional government policy that aims to increase taxpayer compliance and local revenue through the elimination of late vehicle tax payment fines. This study uses a descriptive qualitative research method with a case study approach. Data collection was conducted through in-depth interviews with key informants from the Padang Samsat and supporting informants from the community. The results of this study indicate that the Padang City Samsat has implemented a comprehensive public communication strategy using various media channels. The effectiveness of the communication strategy can be seen from the enthusiasm of the community when participating in this tax amnesty program. However, there are several obstacles for the Padang Samsat in socializing this program so that the community can comply with taxes. There are several obstacles faced by the Padang Samsat in implementing socialization, including difficulties in reaching communities in remote areas with very minimal internet access, low taxpayer awareness and the lack of optimal management for service queues that impact the comfort of the community when participating in this program.